The Structure of Plato’s Republic and the Cave Allegory - Gutiérrez, Raul (Peitho. Examina Antiqua, 2019)
As Plato’s Phaedrus 246c stipulates, every logos must be structured like a living being, i.e., the relation of all its parts to one another and to the whole must be appropriate. Thus, the present paper argues that Plato’s masterwork has been organized in accord with the ascent/descent movement as presented in the Allegory of the Cave: Book I represents eikasia, Books II–IV.434c exemplify pistis, Book IV.434d–444e illustrates dianoia and Books V–VII express noesis. Having reached the anabasis (with the Sun, the Line and the Cave images) the philosopher turns to the consideration of the deficient or unjust forms of the souls and the corresponding political regimes. Finally, the discussion comes back to eikasia through the renewed criticism of mimesis and the exposition of the Myth of Er. As is typical of Plato, this is not merely a formal matter, since the structure conveys that as the Good makes the Ideas intelligible, so the Sun, the Line and the Cave images also throw light on the whole dialogue.